COLLABORATION IN RESEARCH - Bloch, Carter Walter; Andersen, Jens Peter; Ryan, Thomas Kjeldager; Schneider, Jesper Wiborg (CFA Scientific Reports, 2017)
This report seeks to examine the production of research in Denmark, the extent of public-private collaboration and its relation to both scientist’s scientific performance and firm’s economic performance in the period from 1995-2013. The focus of this report is on research measured in terms of scientific publications and research collaboration measured through the co-authorship of publications.